Novel Approach for Detecting Stock Price Movements - Sayyad, Asif G; Wankhade, Nilesh R (International Journal of Computer Sciences and Engineering, 2019)
Grounded on communication theories, we propose to use a data-mining algorithm to detect communication patterns within a company to determine if such patterns may reveal the performance of the company. Specifically, we would like to find out whether or not there exist any association relationships between the frequency of e-mail exchange of the key employees in a company and the performance of the company as reected in its stock prices. If such relationships do exist, we would also like to know whether or not the companys stock price could be accurately predicted based on the detected relationships. To detect the association relationships, a data-mining algorithm is proposed here to mine e-mail communication records and historical stock prices so that based on the detected relationship, rules that can predict changes in stock prices can be constructed. Using the data-mining algorithm and a set of publicly available Enron e-mail corpus and Enrons stock prices recorded during the same period, we discovered the existence of interesting, statistically signi_cant, association relationships in the data. In addition, we also discovered that these relationships can predict stock price movements with an average accuracy of around 80 percent. Given the increasing popularity of social networks, the mining of interesting communication patterns could provide insights into the development of many useful applications in many areas.